Local Wisdom in Sustainable Management of Marine Resources: A Case Study of Coastal Communities in Bone Regency - Hasriyanti, Hasriyanti; Salam, Nunuk Parwati; Sartina, Sartina (LaGeografia, 2021)
Coastal area is an important area to be preserved. Management of coastal areas can be done starting from planning and management must be integrated with socio-cultural, environmental and economic interests. The existence of local wisdom in the community in managing, maintaining and utilizing marine resources can be a filter for modernization that can have a negative impact on social and cultural life as well as the natural environment. The purpose of this paper is to examine and examine the perspective of local wisdom of coastal communities in managing a sustainable environment. The local wisdom of the coastal community of Panyula in sustainable environmental management and is still being carried out today, namely: Mabbaca Doang (Reading Prayers), Massappa Wettu Makanja No Ritasi e' (finding a good or right time to go down to the sea), Appakeng Parewa Tasi Mari Olo (use of traditional fishing gear), and Pemmali Lao No' Ritasi'e (abstinence when going out to sea). This local wisdom has a positive influence on the management, utilization, and sustainable development of marine resources. Where the local wisdom contains the rules or norms and culture of the community that are related and useful in efforts to preserve the sustainable coastal environment.